Produção de amora-preta, sistemas de condução, doses de torta de mamona e concentrações de cálcio e boro - Ferreira, Letícia Vanni (2012)
The blackberry is a rustic specie and despite it has been introduced in Brazil in the 1970, there is few works about the cultural practices of this rosacea were conducted. The aim of this work was to evaluate production and quality of blackberries, using different trellis systems, castor bean pie as fertilization and calcium foliar applications in preharvest. The experiments were conducted at Embrapa Temperate Climate, Pelotas-RS and the chemical analyses, were made at Postharvest Fisiology Laboratory of this institution, from 2010 to 2012. In the first experiment was evaluation the trellis systems type, spaced between row of 0.50 x 3.0m, where the experimental design was in randomized block, with a factorial design 3x3: being three conduction systems (free, trelli and Y ) and three cultivars of blackberry (Tupy, Guarani and Xavante). The cultivar Tupy showed a higher production and fruit flesh average in all conduction systems. The system Y showed better results. In the second experiment was castor bean pie applicated as a base fertilization. The cultivar was cultivar Tupy, using the row spacing as 0.70 x 3m. The treatments were: T1- pattern; T2- 200; T3- 400; T4- 800; T5- 1.600 grams of castor bean pie per plant. The experimental design was randomized blocks. The variables haven t been influenced by castor bean pie. In the third experiment was the calcium foliar application in preharvest. The experimental design was randomized. In 2010 the experiment had four repetitions with eight fruits per repetition, with a factorial design 2x5x2, with two fertilizations levels with and without castor bean pie; five calcium foliar applications x g L-1 (0, 1, 2, 3 and 4 applications), and two storage periods on cold chamber (0 and 3 days). In 2011, there were three repetitions with ten fruits per block, and were doubled the application number of calcium foliar (0, 2, 4 and 8), and it was kept the same concentration per application, and three storage times (0, 3 and 8 days), with a factorial design 2x4x3. During storage there was a reduction of SS of blackberries, and there were significant losses of blackberries mass. The treatment which received a larger number of calcium applications showed a smaller mass loss of fruit. The calcium applications didn t influence the fruit firmness.